ISLAM DAN TANTANGAN MODERNITAS: DINAMIKA NILAI KEAGAMAAN DALAM PERUBAHAN SOSIAL KONTEMPORER - Nur Lailatul Khasanah (LPPM Institut Agama Islam Uluwiyah Mojokerto, 2021)
This article examines the position of Islam in responding to the challenges of modernity, particularly in the context of rapid social changes in politics, culture, education, and religious life. Modernity, driven by the advancement of science and technology, has significantly transformed human lifestyles and worldviews. While modernity offers progress and efficiency, it also brings serious challenges, such as secularization, moral degradation, and spiritual emptiness. Using a qualitative-descriptive approach through literature analysis, this article argues that Islam possesses normative and ethical resources capable of guiding human life amid modern transformations. Islamic values, especially those embedded in education and da‘wah, play a crucial role in maintaining the balance between material progress and spiritual integrity. Therefore, strengthening the role of Islam in modern society is essential to ensure that modernization does not undermine human dignity and moral responsibility.